Pemetaan Tingkat Kebisingan di Uinversitas Islam Negeri Sunan Ampel - Dyah Ratri Nurmaningsih (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
UIN Sunan Ampel is a campus with strategic location, because it is close to various public facility buildings, such as health facilities, offices and entertainment, as well as its presence near public transportation / traffic access which is quite high. This certainly has positive and negative impacts on the campus environment of UIN Sunan Ampel. The positive impact is in the form of ease mobilization for campus community, while one of the negative impacts is noise (noise pollution) caused by traffic around the campus, which can interfere when the teaching and learning process takes place. This research method is quantitative descriptive. Noise data obtained with a sound level meter at 12 sampling points. The data is analyzed by statistical methods and the results are compared with the noise quality standard based on the Decree of the Minister of Environment No. Kep - 48 / MENLH / 11/1996. Then a noise distribution map was made with the application of Surfer 11. The results showed that the value of the noise level at the UIN Sunan Ampel campus had exceeded the permitted quality standard. The noise distribution map shows that the highest noise value is shown in red with the noise level value ≥ 70 dbA. The risk due to noise that occurs at UIN Sunan Ampel campus has exceeded the limit is not conducive environmental condition, such as an impact on learning convenience. So that it is necessary to handle the noise, such as planting trees as a barrier of noise sources and designing a room that are added with soundproof material, that has sound absorbing properties.